2015
DOI: 10.1016/j.corsci.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-pyrrolidine dithiocarbamate on the galvanic coupling resistance of intermetallics – Aluminum matrix during corrosion of AA 2024-T3 in a dilute NaCl

Abstract: a b s t r a c t 1-pyrrolidine dithiocarbamate (PDTC) effect on galvanic coupling resistance of AA 2024-T3 alloy in 0.2 g L À1 NaCl was evaluated by different electrochemical/gravimetric methods and surface analysis. The results obtained from polarization curves and electrochemical quartz crystal microbalance measurements showed that PDTC forms an adsorbed film on the Cu-rich particles, likely through a Cu I -PDTC complex. At high concentrations, PDTC significantly decreases the alloy reactivity thereby providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…In previous works we showed that the protective effect of PDTC might be explained by the formation of a highly stable Cu I -PDTC complex on copper surface that leads to decrease in rate of anodic dissolution and of oxygen reduction reaction [35,36]. Moreover, we carried out similar studies on AA 2024-T3 aluminium alloy that showed good corrosion protection by PDTC thanks to the formation of an adsorbed layer on Cu-rich particles [37].…”
Section: Introductionmentioning
confidence: 88%
“…In previous works we showed that the protective effect of PDTC might be explained by the formation of a highly stable Cu I -PDTC complex on copper surface that leads to decrease in rate of anodic dissolution and of oxygen reduction reaction [35,36]. Moreover, we carried out similar studies on AA 2024-T3 aluminium alloy that showed good corrosion protection by PDTC thanks to the formation of an adsorbed layer on Cu-rich particles [37].…”
Section: Introductionmentioning
confidence: 88%
“…The pitting corrosion can be anticipated. In general, the stage of pitting corrosion is initiated by adsorption of chloride ions on the surface of the oxide layer then the penetration of chloride ions in the oxide layer and the last is a chloride leaching below the surface of the metal oxide layer and essentially [20,21] . Sodium is not corrosive substance.…”
Section: Resultsmentioning
confidence: 99%
“…However, AA5052 alloy has low corrosion resistance. Some aggressive ions such as chloride ions, can attack the alloy surface resulting in corrosion [7]. Corrosion inhibitors are often used as a cost-effective way to protect aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%